2019
DOI: 10.1186/s13104-019-4054-1
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control and correlates in a group of sub Saharan type 1 diabetes adolescents

Abstract: ObjectivesThis study aims to describe the prevalence of glycemic control and related factors in a population of Sub-Saharan African T1D patients. We carried out a cross-sectional study including children and adolescents from seven different centers of the Changing Diabetes in Children (CDiC) program. All children enrolled in the program where recruited after parental consent. Diabetes history, daily practice anthropometrics parameters and HbA1c were assessed for each participant.ResultsWe enrolled 95 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 13 publications
4
22
2
1
Order By: Relevance
“…This is beginning to change with several initiatives now in place across Africa to improve the management of patients with diabetes. These include patient led strategies to strengthen healthcare systems, strategies to improve guideline adherence where there are concerns with suboptimal management, assist patients with appropriate lifestyle changes including diet and exercise, provide free medicines and diagnostic equipment as well as instigate quality targets (7,20,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Country Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…This is beginning to change with several initiatives now in place across Africa to improve the management of patients with diabetes. These include patient led strategies to strengthen healthcare systems, strategies to improve guideline adherence where there are concerns with suboptimal management, assist patients with appropriate lifestyle changes including diet and exercise, provide free medicines and diagnostic equipment as well as instigate quality targets (7,20,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Country Epidemiologymentioning
confidence: 99%
“…These include failure to seek help, unavailability of regular screening programmes for patients suspected of having T1DM, inability to make a formal diagnosis, inadequate and inappropriate care exacerbated by the lack of equipment, facilities and professionals, e.g. Ghana currently has less than fifteen endocrinologists, poor knowledge among patients and parents, frequent episodes of hypoglycaemia exacerbated by a lack of insulin and the cost of insulin as well as monitoring sticks and syringes, poor storage of insulin, poor adherence to treatments and poor eating habits as well as cultural aspects of care (1,6,20,24,43,44,62,63,80,(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). The WHO in 2015 found that in SSA only 51% of the countries had metformin routinely available and only 40% had insulin readily available, well below the 80% target (1, 105).…”
Section: Country Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Parents expect adolescents with T1D to become independent with diabetes control, although adolescents with T1D struggle to manage diabetes without the supervision of parents and healthcare providers. Compared with other age groups, adolescents with T1D have worse glycemic control (Djonou et al, 2019; Lee et al, 2020), with only 18.1%–32.6% of adolescents with T1D meeting the ADA guidelines for target HbA1c) levels (Djonou et al, 2019; Lee et al, 2020). Understanding the factors and pathways associated with subsequent HbA1c levels could assist in the development of comprehensive and timely interventions to improve glycemic control among this population.…”
Section: Introductionmentioning
confidence: 99%
“…Em seguida, após leitura do texto completo, foram excluídos outros 23 artigos, por se tratarem de estudos de comparação de métodos laboratoriais, estudos de intervenção, artigos de revisão, estudos que trabalharam com média de HbA1c ou glicemia de jejum, estudos onde a HbA1c foi auto referida, estudos em populações muito específicas, como, por exemplo, pessoas com Índice de Massa Corporal >25kg/m², pacientes críticos e em Unidade de Terapia Intensiva, pessoas encarceradas, pacientes com doença renal e pessoas com carência de vitamina D.Portanto, ao final da seleção foram incluídos um artigo da base de dados LILACS e 36 artigos da base de dados PubMed. Dos 37 artigos selecionados, seis artigos(CARLSEN et al, 2017;DJONOU et al, 2019;FISHER et al, 2018; MAIORINO et al, 2018;SZADKOWSKA et al, 2018;YETIM et al, 2018) mostraram a prevalência de controle glicêmico adequado em crianças, adolescentes e adultos jovens com Revisão da literatura: estudos sobre prevalência de controle glicêmico adequado em pessoas com diabetes mellitus tipo 1…”
unclassified